Inhibition of anandamide hydrolysis does not rescue respiratory abnormalities observed in an animal model of Parkinson's disease. Issue 2 (30th December 2021) - Batista, Luara A.; Cabral, Laís M.; Moreira, Thiago S.; Takakura, Ana C.
Abstract : New Findings: What is the central question of this study? The respiratory frequency to hypercapnia is attenuated in an animal model of Parkinson's disease (PD): what is the therapeutic potential of inhibition of anandamide hydrolysis for this respiratory deficit? What is the main finding and its importance? In an animal model of PD there is an increased variability in resting respiratory frequency and an impaired tachypnoeic response to hypercapnia, which is accompanied by diminished expression of Phox2b immunoreactivity in the retrotrapezoid nucleus (RTN). Inhibition of anandamide hydrolysis also impaired the response to hypercapnia and decreased the number of Phox2b immunoreactive cells in the RTN. This strategy does not reverse the respiratory deficits observed in an animal model of PD. Abstract: Parkinson's disease (PD) is characterized by severe classic motor symptoms along with various non‐classic symptoms. Among the non‐classic symptoms, respiratory dysfunctions are increasingly recognized as contributory factors to complications in PD. The endocannabinoid system has been proposed as a target to treat PD and other neurodegenerative disorders. Since symptom management of PD is mainly focused on the classic motor symptoms, in this work we aimed to test the hypothesis that increasing the actions of the endocannabinoid anandamide by inhibiting its hydrolysis with URB597 reverses the respiratory deficits observed in an animal model of PD. Results show that bilateral injection of 6‐hydroxydopamine hydrochloride (6‐OHDA) in the dorsal striatum leads to neurodegeneration of the substantia nigra, accompanied by reduced expression of Phox2b in the retrotrapezoid nucleus (RTN), an increase in resting respiratory frequency variability and an impaired tachypnoeic response to hypercapnia. URB597 treatment in control animals was associated with an impaired tachypnoeic response to hypercapnia and a reduced expression of Phox2b in the RTN, whereas treatment of 6‐OHDA‐lesioned animals with URB597 was not able to reverse the deficits observed. These results suggest that targeting anandamide may not be a suitable strategy to treat PD since this treatment mimics the respiratory deficits observed in the 6‐OHDA model of PD.